Indigenous autonomous zones, original nations and the local political system. The case of the Kirkyawi ayllu (Bolivia) - Nelson Antequera (CUHSO)
The general aim of this work is to contribute to understand the political transformations of theindigenous communities of the Andean region of Bolivia since the state reforms implemented in the decade of1990 and in a perspective that focuses in how the indigenous community, in our case the ayllu Kirkyawi, havepolitically reshaped in the new legal, institutional and political frame. We show that it is the “community”constructed from its own political system the one that might constitute juridically as “nation” in thecontext of the new Estado Plurinacional. That means that it’s necessary to go beyond the “recognition” ofthe ethnic and cultural diversity to the construction of a political and administrative system that opens thepossibility of the construction of a real indigenous autonomy; that’s to say, to determine the indigenousnations’ own political system, authorities system, the instances of participation and decision making andtheir own legislative practices; in a word, the possibility of self determination. This is the political projectthat arises from the community for the constitution of the nations of the Estado Plurinacional.